2006
DOI: 10.1029/2006gl025994
|View full text |Cite
|
Sign up to set email alerts
|

Changes in surface ozone levels due to convective downdrafts over the Bay of Bengal

Abstract: [1] Simultaneous measurements of surface level ozone (O 3 ) and meteorological parameters were made over the Bay of Bengal (BOB) during a cruise between 14 September and 12 October 2002. Variations in surface O 3 , equivalent potential temperature (q E ) and associated meteorological parameters clearly show evidence of convective downdrafts during 18-19 September and 25-26 September. Sharp increase in O 3 mixing ratio is coupled with decrease in q E value in the detrained air. The vertical wind velocity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…The post-monsoon season had the second highest O 3 concentrations suggesting the impact of biomass burning over IGB region providing significant reactive hydrocarbon species concentrations , Bisht et al, 2015Tiwari et al, 2015b). O 3 concentrations were comparable to those reported at other urban locations in India (Chelani, 2013;Debaje and Kakade, 2009;Beig et al, 2007;Sahu and Lal, 2006;Lal et al, 2012; references therein) as well as urban areas in China (Tu et al, 2007;Tang et al, 2009), but lower than rural and high altitude sites in India where NO emissions are much lower (24-36%) (Kumar et al, 2010a, b;Reddy et al, 2010). In Delhi, the mean O 3 concentration was much higher (23.6 ppb) than the Patna (Tiwari et al, 2015a) (Table 2).…”
Section: Meteorological Datasupporting
confidence: 85%
“…The post-monsoon season had the second highest O 3 concentrations suggesting the impact of biomass burning over IGB region providing significant reactive hydrocarbon species concentrations , Bisht et al, 2015Tiwari et al, 2015b). O 3 concentrations were comparable to those reported at other urban locations in India (Chelani, 2013;Debaje and Kakade, 2009;Beig et al, 2007;Sahu and Lal, 2006;Lal et al, 2012; references therein) as well as urban areas in China (Tu et al, 2007;Tang et al, 2009), but lower than rural and high altitude sites in India where NO emissions are much lower (24-36%) (Kumar et al, 2010a, b;Reddy et al, 2010). In Delhi, the mean O 3 concentration was much higher (23.6 ppb) than the Patna (Tiwari et al, 2015a) (Table 2).…”
Section: Meteorological Datasupporting
confidence: 85%
“…Over Amazonia with its high degree of convective activity, downdrafts are likely to play a more important role. Downward transport of UT air by downdrafts associated with deep convective activity has been shown to inject air with lower moisture content, lower equivalent potential temperature, and elevated O 3 into the PBL (Zipser, 1977;Betts et al, 2002;Sahu and Lal, 2006;Grant et al, 2008;Hu et al, 2010;Gerken et al, 2016). It would follow that the same mechanism also brings down aerosol-rich air from the UT into the PBL.…”
Section: Conceptual Model and Role In Aerosol Life Cyclementioning
confidence: 93%
“…Betts et al, 2002;Sahu and Lal, 2006;Hu et al, 2010), only few report on downward mixing from the tropical stratosphere. Lu et al (2000) showed with 2-D cloud resolving modelling that convective towers that reach the tropical tropopause have the potential to transfer ozone-rich air down into the cloud anvil.…”
Section: Transport and Mixingmentioning
confidence: 99%